2022
DOI: 10.1186/s13045-022-01313-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial adaptation in cancer drug resistance: prevalence, mechanisms, and management

Abstract: Drug resistance represents a major obstacle in cancer management, and the mechanisms underlying stress adaptation of cancer cells in response to therapy-induced hostile environment are largely unknown. As the central organelle for cellular energy supply, mitochondria can rapidly undergo dynamic changes and integrate cellular signaling pathways to provide bioenergetic and biosynthetic flexibility for cancer cells, which contributes to multiple aspects of tumor characteristics, including drug resistance. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 609 publications
(374 reference statements)
1
56
0
Order By: Relevance
“…Strikingly, the immunoblot and LDH release assay results of laser irradiation could be significantly rescued by NAC (Figures S6B,D and S8D–E), suggesting that ROS was the driving element to induce cell pyroptosis. All of the results elucidated the underlying mechanism that the A-C/NPs triggered ROS generation under NIR laser irradiation to induce pyroptosis through damaging the homeostasis of the mitochondrial pathway, thus exhibiting satisfactory antitumor potential in vitro .…”
Section: Resultsmentioning
confidence: 89%
“…Strikingly, the immunoblot and LDH release assay results of laser irradiation could be significantly rescued by NAC (Figures S6B,D and S8D–E), suggesting that ROS was the driving element to induce cell pyroptosis. All of the results elucidated the underlying mechanism that the A-C/NPs triggered ROS generation under NIR laser irradiation to induce pyroptosis through damaging the homeostasis of the mitochondrial pathway, thus exhibiting satisfactory antitumor potential in vitro .…”
Section: Resultsmentioning
confidence: 89%
“…3D, E). Recent evidence suggests that the metabolic pattern is crucial for chemo-resistance in cancers [22]. As a rate-limiting enzyme, α-KGDC activity may induce alterations in the ux of metabolites through TCA.…”
Section: Resultsmentioning
confidence: 99%
“…α-KGDC represents a major modulator of ETC activity and TCA cycle ux, and is a pivotal enzyme in the metabolic reprogramming [20], and its activation suppressed via the hypoxia-inducible factor 1 (HIF1) could impede tumor growth in vivo [21]. DLDH, as its E3 subunit, is involved in the decarboxylation of pyruvate to form acetyl-CoA and reduced NAD to NADH during the cascade of glucose metabolism and mitochondrial ATP production [18,22]. Our study revealed that EVs-DLDH was delivered and enriched in the mitochondria of the recipient cells, promoting the activity of α-KGDC and NADH production (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is well reported that apoptotic cell death is mediated by autophagy, which occurs prior to apoptosis in chemosensitive tumor cells but not in chemoresistant tumor cells since mitochondrial remodeling has been confirmed [ 219 ]. Typically, autophagy induced by mitochondrial remodeling often causes treatment failure that is associated with drug resistance to common chemotherapeutic drugs including CDDP, DOX, 5-FU, and PTX [ 220 ].…”
Section: Autophagy: a Novel Force Triggering Drug Resistancementioning
confidence: 99%